The Enhancement Solubility and Stability of Erythromycin Formatted in Solid Lipid Nanoparticles by Utilizing PVA as Stabilizer - Mardiyanto; Budi Untari; Najma Fithri Annuria; Ady Mara; Andre Agung Aprianto; Gustina Emilia Ningsih (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2022)
Infectious diseases have changed the world order today where the infection is the main cause of illness and death in the world. Erythromycin is a macrolide antibiotic that can generally inhibit the growth of Staphylococcus aureus and resistant strains. The free molecule of erythromycin in the part of the body does not reach Staphylococcus aureus because it is degraded by the first-pass effect. Nanoparticles can minimize damage to active substances due to first-pass effects because the particles have been protected by biopolymers leading to the minimizing damage of active substances. Formulation of nanoparticles loading erythromycin was used with the following variations in the amount of erythromycin 25 to 100 mg. Erythromycin was formulated by the coated polymer to changes the physics of the erythromycin into a particle. Preparation of erythromycin into nanoparticles was utilized stearic acid polymer, PEG-400, and polyvinyl alcohol using hot homogenization and ultrasonication method. Results showed that the optimum formula was the second formula (F2) with a percentage of encapsulation efficiency of 80.89773±0.11364. The results of the characterization of submicron particle formation such as morphology, diameter (particle size) and distribution (PDI) of F2 were spherical 518.6 nm; 0.096 PDI; and a zeta potential value of -12 mV respectively. The particles loading erythromycin were successfully increasing the stability of erythromycin for up to 5 cycles in terms of the heating-cooling-cycles test and also the solubility in SIF.